7m+2m+8m-6=

Simple and best practice solution for 7m+2m+8m-6= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7m+2m+8m-6= equation:


Simplifying
7m + 2m + 8m + -6 = 0

Reorder the terms:
-6 + 7m + 2m + 8m = 0

Combine like terms: 7m + 2m = 9m
-6 + 9m + 8m = 0

Combine like terms: 9m + 8m = 17m
-6 + 17m = 0

Solving
-6 + 17m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 17m = 0 + 6

Combine like terms: -6 + 6 = 0
0 + 17m = 0 + 6
17m = 0 + 6

Combine like terms: 0 + 6 = 6
17m = 6

Divide each side by '17'.
m = 0.3529411765

Simplifying
m = 0.3529411765

See similar equations:

| .95=logx | | 55*1=n | | 5x-16+3x=180 | | 4x-12=6x-36+14 | | -3x+12= | | -9f+(-32)=-95 | | 3+2h=5 | | 2n+7-7n=33-11n+10 | | 3+-1u=0 | | 2t-4t=8 | | 8g-15=73 | | 1+-4u=0 | | 8c-(-19)=59 | | s=6*7+64t-16t^2 | | 1.5(9x-3)=-4+8x | | h+30=180 | | 8c-(-19)=58 | | 5x+3=-x-2 | | -8+2g=-2 | | 5x+5=-10forx | | 2(w+5)=12 | | 4(x-a)+5b=5x+aforx | | ps+qr=r | | 15-5y=y+11+3y | | X+7=3x+11 | | 2x-(3+4x)=7 | | 10*K-5*k=1 | | 4z-6=5z | | P^3+125= | | 8xsquared+x= | | 2x^4+2x-17x=-3 | | 3(2x+7)=30 |

Equations solver categories